The effects of dexmedetomidine infusion on the formation of reactive oxygen species during mesenteric ischemia-reperfusion injury in rats - (:unkn) unknown (My University, 2007)
Objective: The aim of this study was to evaluate the effect of dexmedetomidine infusion on the formation of reactive oxygen species during mesenteric ischemia-reperfusion injury in rats. Methods: Twenty-eight male Sprague-Dawley rats weighing between 300-320 g were divided into four groups (n=7). The first two groups underwent sham operation; group 1 was the control group and group 2 received 5 μg/kg/h dexmedetomidine iv infusion. Ischemia-reperfusion (I/R) was produced in the remaining two groups (group 3 and 4) by ligation of the superior mesenteric artery for 30 min followed by 60 min of reperfusion period. Group 3 (I/R-S) rats were control I/R rats receiving 0.9% NaCl infusion and group 4 (I/R-D) rats received 5 μg/kg/h dexmedetomidine iv infusion during I/R. Tissue samples were obtained from the ileum for the measurement of luminol and lucigenin enhanced chemiluminescence (CL), tissue myeloperoxidase activity, malondialdehyde (MDA) and glutathione levels. Results: Luminol CL levels, tissue myeloperoxidase activity (p<0.05). and MDA levels (p<0.05) were significantly higher in I/R-S group compared with sham-operated groups and I/R-D group. Glutathione levels of I/R-S group was significantly higher than those of I/R-D group (p<0.05). Conclusion: We concluded that dexmedetomidine infusion can prevent the increase in reactive oxygen species during mesenteric ischemia-reperfusion injury in rats.
Keywords: α2-adrenergic agonists; Dexmedetomidine; Ischemia-reperfusion injury; Reactive oxygen species